b - Golbeck, Susan L. (b)
The field of early childhood education and the science of psychology have a long and closely intertwined history. The study of young children's learning within school contexts provides a test of developmental theory while at the same time identifies the l.
Includes bibliographical references and index.
Keywords: Early childhood education -- -- -- -- Psychological aspects -- Congresses. -- United States; Early childhood education -- Psychological aspects